Conservation strategies for endangered arable plant Euphorbia gaditana - Sonia G. Rabasa; Rut Sánchez de Dios; Francisco José Cabezas Fuentes; María Beatriz Pías Couso; Felipe Domínguez Lozano (Conservation Science and Practice, 2022)
Abstract Fragmentation and habitat loss are considered among the most important threats to biodiversity. More precisely, transformation of natural habitats into farmlands has been identified as one of the primary causes of plant species extinction. Therefore, understanding the effects of habitat fragmentation is crucial to the successful conservation of threatened species. Metapopulation modeling is one of the prospective tools used in conservation biology to evaluate long‐term survival in fragmented landscapes. In this work, we applied a metapopulation approach to the conservation of the rare plant Euphorbia gaditana Coss., an endangered species growing on the margins of crops in southern Spain. The species is threatened due to herbicide application and intensification of cultivation, which results in a highly patchy distribution, with more than 50 patches of habitat across three separate networks of patches. We used IFM (Incidence Function Modeling) to compare the relative effectiveness of four conservation management scenarios and the effect of three threat scenarios on the risk of extinction of the species. The results of our simulations of population dynamics under plausible management scenarios will aid conservation decision‐making, for example, allowing priority conservation areas to be identified or assessing the effect of future reintroductions.